TOPENG PASIR ANGIN MENEMBUS BATAS: FUNGSINYA DALAM KEHIDUPAN MANUSIA - Goenadi Nitihaminoto (BRIN, 2006)
The gold masks found at the Pasir Angin Site are still intact, because they are made of a precious metal that is hard to rust, which is resistant to physical and chemical effects that gnaw at for thousands of years and does not undergo corrosion causing damage. What if the mask was made a duplicate and then used. I totally agree, because in my opinion the conditions that support it are quite adequate. We return the copy of the mask along with other findings to its place of origin, in a small artistic building (museum building), which we use as tourism. Pasir Angin site, which is located on a hill, has a part in the tourism element, namely natural tourism. From the top of the hill, visitors can freely view the natural scenery around it. In the middle of that small hill, a small building was built as a mini museum.